2018
DOI: 10.1007/s10143-018-0953-1
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive epidemiology of glial tumors may reveal novel treatments: high-dose progestins or progesterone antagonists as endocrino-immune modifiers against glioma

Abstract: Female gender, contraceptives, and menopausal hormone replacement treatments containing progesterone analogues associate with higher risk of meningiomas yet with lower risk of gliomas. Progesterone receptor (PR) expression and mifepristone treatment was highly discussed for meningiomas. However, much less is known in regard to progesterone actions in gliomas despite PR expression strongly correlates with their grade. Meningiomas and gliomas may grow faster during gestation; but paradoxically, parousity reduces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 109 publications
1
28
0
Order By: Relevance
“…No related studies have shown that it is related to the occurrence and development of GBM. However, previous research has established that downstream cholesterol and sterol hormones regulated by 00100_6 will affect the progression of GBM ( 35 , 55 58 ). In addition, vitamin D metabolism is directly regulated by calcidiol 1-monooxygenase ( CYP27B1 ) and vitamin D 1,25-hydroxylase ( CYP105A1 ) downstream of the metabolic subpathway 00100_6, and studies have shown that the level of 25-hydroxyvitamin D (25(OH)D) in the serum of intermediates of vitamin D metabolism is opposite to that of patients with GBM-specific subtypes ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…No related studies have shown that it is related to the occurrence and development of GBM. However, previous research has established that downstream cholesterol and sterol hormones regulated by 00100_6 will affect the progression of GBM ( 35 , 55 58 ). In addition, vitamin D metabolism is directly regulated by calcidiol 1-monooxygenase ( CYP27B1 ) and vitamin D 1,25-hydroxylase ( CYP105A1 ) downstream of the metabolic subpathway 00100_6, and studies have shown that the level of 25-hydroxyvitamin D (25(OH)D) in the serum of intermediates of vitamin D metabolism is opposite to that of patients with GBM-specific subtypes ( 59 ).…”
Section: Discussionmentioning
confidence: 99%
“…2 Even though pregnancy may accelerate GBM growth, parity lowers the lifelong risk of GBM, which may associate with the fact that high dose and prolonged exposure to P4 may eliminate cells leading to GBM growth. 2 Based on fine structural features, P4 is proposed to induce an oligodendroglial differentiation shift in GBM cells. 7 Despite the P4 receptor is a steroid receptor that has the highest correlation with glial tumor grade 2,15 ; there exist surprisingly few studies which assessed the effects of P4 on the biological behavior of GBMs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite some controversies, many available studies demonstrate that female gender, parity, and hormone replacement treatment reduce the risk of GBMs, while the reverse is true for meningiomas. 1,2 In pregnancy, the levels of progesterone (P4) gradually increase up to 200-fold to around 160 µM. Even though pregnancy may accelerate the growth of gliomas, the most angiogenic brain tumors are encountered lesser during the last trimester when the natural 17-OH-progesterone levels reach peak levels.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor fragments were implanted at day 1 and tumor growth was monitored for each experimental group at the time indicated by measuring the average tumor diameter (two perpendicular axes of the tumor were measured by a Vernier caliper). The volume of the tumor is reported in mm 3 according to the formula 4/3pr 3 .…”
Section: Animals and In Vivo Experimentsmentioning
confidence: 99%
“…The presence of hormone receptors in neoplastic cells, which can interfere with cell growth, opens new perspectives in the control of tumors (2). Thus, hormones such as progesterone and cortisol have been reported to influence cell growth in various types of tumors (3,4). For instance, it has been reported that high doses of natural progesterone inhibit the growth of human neuroblastoma cells (SK-N-AS) both in vitro and in vivo by suppression of cell proliferation and induction of apoptosis (4).…”
Section: Introductionmentioning
confidence: 99%